Priapism Case Report on Chronic Myelocytic Leukemia With Winter Procedure Management - Pratama, Dio Rancha; Jouwena, Davis Roland Gustav; Taher, Taufik Rakhman (Jurnal Health Sains, 2023)
Objective: We reported a case of priapism fracture in chronic myelocytic leukemia performed winter procedure Case presentation: We reported a 22-year-old male patient with complaints of erect penis continuously for 3 days without being affected by sexual stimulation. The patient feels pain in his penis and can still urinate. The patient denied any previous history of penile trauma, drug use, and similar complaints. Physical examination found an erect penis with EHS 4 and palpable corpus cavernosum stiff and soft. Routine blood support tests show an increase in leukocytes up to 367,000/μL. Examination of peripheral blood images shows an increase in the number of all types of granulocytes from young cells to blast cells with the effect of a chronic leukemia. Intracavernous blood gas analysis showed pH 7.2, pO2 25 mmHg, and pCO2 75 mmHg. Based on data obtained from the anamnesis, physical examination, and supporting examinations, a diagnosis of ischemic or low flow priapism was established. The patient was treated with cavernous blood aspiration using the winter procedure and combined with intracavernous irrigation using the α phenyleprine agonist. Discussion: The patient performed a winter procedure using two 18G needles for cavernous blood aspiration and combined with intracaevernose irrigation using phenylephrine 1 mg diluted saline. Intracavernous blood aspiration gets 40 mL of blood. The action was performed in the operating room for 2 hours with the result of the penis being detumescence with EHS 2. The patient is observed for 2 days and then referred to a hospital with internal medicine specialist facilities, hemato-oncology consultants for further management related to CML. Conclusion: Ischemic type priapism or low flow is a urological emergency that can be managed with winter procedures and shows good outcomes.